Molecular specific and sensitive detection of pyrazinamide and its metabolite pyrazinoic acid by means of surface enhanced raman spectroscopy employing in situ prepared colloids - Muehlig, Anna; Jahn, Izabella J.; Heidler, Jan; Jahn, Martin; Weber, Karina; Sheen, Patricia; Zimic, Mirko; Cialla-May, Dana; Popp, Jürgen (Applied Sciences, 2019)
The prodrug pyrazinamide (PZA) is metabolized by the mycobacteria to pyrazinoic acid (POA), which is expelled into the extracellular environment. PZA resistance is highly associated to a lack of POA efflux. Thus, by detecting a reduction of the concentration of POA in the extracellular environment, by means of lab-on-a-chip (LoC)-SERS (surface-enhanced Raman spectroscopy), an alternative approach for the discrimination of PZA resistant mycobacteria is introduced. A droplet-based microfluidic SERS device has been employed to illustrate the potential of the LoC-SERS method for the discrimination of PZA resistant mycobacteria. The two analytes were detected discretely in aqueous solution with a limit of detection of 27 μm for PZA and 21 μm for POA. The simultaneous detection of PZA and POA in aqueous mixtures could be realized within a concentration range from 20 μm to 50 μm for PZA and from 50 μm to 80 μm for POA.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Drug resistant mycobacteria; Lab-on-a-Chip (LoC); Personal medicine; Quantitative SERS detection of PZA and POA; Surface-enhanced Raman spectroscopy (SERS)